Analyzing of Scrabble Go Application as a Media of English Language Teaching - Dzu Al Mirroh; Wildan Isna Asyhar; Erwin Hari Kurniawan (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
This paper examines the potential of Scrabble GO, a popular mobile adaptation of the classic word game Scrabble, as a tool for enhancing English language education. It analyzes the game's features and mechanics, exploring how they align with established principles of language acquisition and English skills. By drawing upon relevant research in second language acquisition and game-based learning, the paper evaluates the use of Scrabble GO in promoting vocabulary development and spelling accuracy. It also considers the game's potential to foster motivation, engagement, and communicative competence among learners. The paper concludes by discussing the limitations of Scrabble GO in English language education and proposing strategies for maximizing its uses within different learning contexts.